Distinctive diet‐tissue isotopic discrimination factors derived from the exclusive bamboo‐eating giant panda. Issue 6 (November 2016) - HAN, Han; WEI, Wei; NIE, Yonggang; ZHOU, Wenliang; HU, Yibo; WU, Qi; WEI, Fuwen
Abstract: Stable isotope analysis is very useful in animal ecology, especially in diet reconstruction and trophic studies. Differences in isotope ratios between consumers and their diet, termed discrimination factors, are essential for studies of stable isotope ecology and are species‐specific and tissue‐specific. Given the specialized bamboo diet and clear foraging behavior, here, we calculated discrimination factors for carbon and nitrogen isotopes from diet to tissues (tooth enamel, hair keratin and bone collagen) for the giant panda ( Ailuropoda melanoleuca ), a species derived from meat‐eating ancestors. Our results showed that carbon discrimination factor obtained from giant panda tooth enamel (ε 13 Cdiet‐enamel = 10.0‰) and nitrogen discrimination factors from hair keratin (Δ 15 Ndiet‐hair = 2.2‰) and bone collagen (Δ 15 Ndiet‐collagen = 2.3‰) were lower, and carbon discrimination factors from hair keratin (Δ 13 Cdiet‐hair = 5.0‰) and bone collagen (Δ 13 Cdiet‐collagen = 6.1‰) were higher than those of other mammalian carnivores, omnivores and herbivores. Such distinctive values are likely the result of a low‐nutrient and specialized bamboo diet, carnivore‐like digestive system and exceptionally low metabolism in giant pandas.